The Personification of Paidia in Attic Pottery. The Playful Experience in the World of Dionysus and Aphrodite - Giovanna Camponetti (Pallas, 2022)
The personification of Paidia is represented in Attic pottery between 430 and 390 BC in the sphere of two divinities, Dionysus and Aphrodite, and with two different iconographies. In the Dionysian world, she is a maenad and often appears in the thiasos, but also in mythological accounts such as the Gigantomachy. She represents the personified concept of the playful experience of dance, music, and theatrical performance. In the sphere of Aphrodite, Paidia is a young woman, richly dressed; she appears in domestic or ritual scenes, acting in view of the wedding preparations. She gives necklaces and symbolises the young woman who leaves the world of childish play to become a gynè. The representations are closely linked to the Athenian cult shrines of Aphrodite, Eukleia and Eunomia to which precise references are made.